Autoimmune thyroid disease and urticarial vasculitis: is there a significant association? - Cherrez-Ojeda, Iván; Cherrez, Sofia (Allergy, asthma and clinical immunology, 2019)
Little is known about the association of urticarial vasculitis (UV) with thyroid autoimmunity. The latter has been mostly described in the setting of patients with chronic spontaneous urticaria (CSU). In this letter to the editor, we compare UV and CSU through retrospective analyses, which reveal that 41.7% patients with UV presented antithyroperoxidase (anti-TPO) and/or antithyroglobulin antibody (ATA) above the reference range, while only 4% patients with CSU had these antibodies elevated. There is a moderately strong association assessed by the Phi coefficient (φ = 0.420, p = 0.004). Further research is needed to appropriately address the relationship between UV and thyroid autoimmunity and explore any potential underlying pathophysiological process between both diseases.
Gesehen am 10.05.2019